Investigating the risk and resilience of flash flood in Sunamgonj haor region of Bangladesh - Islam, MR; Babu, MAH; Uddin, MJ; Khatun, ML; Islam, MS (International Journal of Agricultural Research, Innovation and Technology, 2021)
Bangladesh faces various types of natural hazards from its birth due to geographical location and physiographic conditions. Flood is the most common event among them. Northeastern part of Bangladesh faces flash flood almost every year with large scale of damage. Tanguar haor, (a famous Ramsar site of Bangladesh) located in Tahirpur upazila of Sunamgonj district. This wetland adjacent area is the most vulnerable zone in terms of flash flood hazard. About more than 80%, people are the direct victim of this hazard. The aim of this study was to assess the risk and resilience status of flash flood at community level. A risk and resilience assessment matrix leads to fulfill the assessment where only primary data were used. A comparative study between those statuses is computed based on Pearson correlation of co-efficient analysis that presents the difference of risk and resilience of the study area that helps to realize the emergence of flash flood risk reduction. The findings of this study will be a pathway for the policy makers, local administrators for the development of sustainable community level risk management, policy-making and its implementations. Int. J. Agril. Res. Innov. Tech. 10(2): 47-53, December 2020